Growth, yield and nutrition of sugarcane ratoon as affected by potassium in a mechanized harvesting system - Pancelli, Márcio Alexandre [UNESP]; Prado, Renato de Melo [UNESP]; Flores, Rilner Alves; de Almeida, Hilário Júnior [UNESP]; Moda, Leandro Rosatto [UNESP]; de Souza Junior, Jonas Pereira [UNESP] (My University, 2015)
Sugarcane mechanical harvest deposes straw residue on the soil surface, increases soil organic matter and improves nutrients cycling, especially potassium (K). The objective of this work was to evaluate the effect of K fertilizer on vegetative growth, mineral nutrition, straw yield and technological quality; i.e., levels of total soluble solids, industry fiber (bagasse), apparent sucrose, juice purity, and reducing sugars in a ratoon sugarcane grown in Oxisol in a mechanized harvesting system. The experiment design was carried out in the 2009/10 cropping season in the state of São Paulo, Brazil, in the first regrowth of sugarcane after harvest using cultivar RB 86-7515. The experimental design was a randomized block with five replicates and five rates of K-fertilizer: 0 (control); 32.5; 65.0; 130.0 and 195.0 kg ha-1 of K2O. Potassium levels in the soil and in the plant, stalk production and the technological quality were evaluated at harvest. The rate of 195 kg ha-1 of K2O increased in 279, 78, 142 and 29% the K exchangeable content in the 0-20 and 20-40 cm layers at 180 and 360 DAS, respectively, increased soil potassium availability and promoted higher absorption of nutrients by plants, reaching 9.8 g kg-1 in leaves; i.e. 22.6% higher compared to the control treatment. The higher absorption of potassium was reflected on yield gain of 28.6% with 147.5 kg ha-1 of K2O. Therefore, 130 kg ha-1 of K2O is the most appropriate rate for the production of stalks of sugarcane grown in an Oxisol within the range evaluated. This rate kept potassium nutritional status very close to the adequate and promoted its accumulation in stalks at levels considered satisfactory to reach high yields in the first ratoon. Potassium fertilization had little effect in the technological quality.
Keywords: Conservationist system; Plant nutrition; Potassium fertilization; Potassium nutrition; Saccharum spp